2013
DOI: 10.1016/j.njas.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable production in the Red River Delta of Vietnam. II. Profitability, labour requirement and pesticide use

Abstract: Vegetable production plays an important role in the rural economy of the Red River Delta (RRD), Vietnam. Data were collected on present vegetable production in the RRD, with the aim to characterise the vegetable production in terms of profitability, labour requirement and pesticide use and to evaluate vegetable production for its potential to increase rural household income.Three hundred and sixty data sets consisting of qualitative (planting and harvesting dates) and quantitative (yield, product price, materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Data collected on the profitability of vegetable production showed that vegetable production can raise family income (Huong et al. ). The low labour requirement scenario for the ‘ Labour ’ system. Crops grown in this scenario have a low labour requirement.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data collected on the profitability of vegetable production showed that vegetable production can raise family income (Huong et al. ). The low labour requirement scenario for the ‘ Labour ’ system. Crops grown in this scenario have a low labour requirement.…”
Section: Methodsmentioning
confidence: 99%
“…The data used on crop‐specific pesticide input were related to the costs of the pesticides used, as farmers sometimes had no good recollection of active ingredients or trademarks used, but always were able to provide data on pesticide expenses (Huong et al. ). The high level of biodiversity scenario for the ‘ Biodiversity ’ system. Soil‐borne diseases can be controlled effectively through crop rotation, for example, Fusarium wilt caused by Fusarium oxysporum is a common disease in the RRD (Oanh et al.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations